Retirement Savings Model Tested With Brazilian Private Health Care Workers - Schuabb, Thais C.; França, Lucia H.; Amorim, Silvia M. (Frontiers in Psychology, 2019)
Retirement is one of the most serious challenges facing Brazil currently, considering the rapid pace of population aging, growing social inequalities, and the difficulty that Brazilians have in planning for their financial future. The number of studies on psychosocial factors in retirement is limited. The aim of this cross-sectional study is to determine Brazilian health workers’ perceptions about financial planning for retirement, based on studies by Hershey and Mowen (2000). In this study, retirement saving – the dependent variable - is highlighted by the use of a model with the following antecedents: parental influence, retirement goal clarity and retirement planning activity level. The goals of the study were to establish mediating and moderating relationships as an innovative approach to the original model. Data was gathered from 319 workers at a private hospital in the municipality of Niterói, Rio de Janeiro (Brazil) who filled out a questionnaire concerning their saving behaviors and antecedents. Results indicated a model in which goal clarity mediated the relationship between parental influence and retirement saving, and retirement activity was observed to influence the level of retirement saving. The findings confirmed the complexities of financial planning for retirement, and emphasized important factors, such as parental advice starting in childhood and the effect of this advice on goal clarity. The results also pointed to the role of individual responsibility in the process, which depended on establishing a plan for activities. In addition to parental advice, an educational approach can contribute encouraging saving behaviors and helping retirees achieve financial security in retirement.